1995
DOI: 10.1002/ijc.2910610305
|View full text |Cite
|
Sign up to set email alerts
|

The presence of persistent high‐risk hpv genotypes in dysplastic cervical lesions is associated with progressive disease: Natural history up to 36 months

Abstract: To evaluate the clinical significance of HPV genotyping for the prediction of progressive cervical intraepithelial neoplasia (CIN) in women with cytomorphologically abnormal smears, a prospective, blind, non-intervention study was performed. A total of 342 patients screened with cytomorphologically abnormal cervical smears were monitored every 3-4 months by cervical cytology, colposcopy and HPV testing using PCR. Women with progressive CIN disease were defined as patients developing lesions with a colposcopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
212
1
3

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 333 publications
(225 citation statements)
references
References 25 publications
(24 reference statements)
9
212
1
3
Order By: Relevance
“…Women were monitored every 3 to 4 months by cytology, colposcopy and HPV testing (Remmink et al, 1995;Nobbenhuis et al, 1999Nobbenhuis et al, , 2001. Clinicians and laboratory staff were blinded for HPV test results and clinical findings, respectively.…”
Section: Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Women were monitored every 3 to 4 months by cytology, colposcopy and HPV testing (Remmink et al, 1995;Nobbenhuis et al, 1999Nobbenhuis et al, , 2001. Clinicians and laboratory staff were blinded for HPV test results and clinical findings, respectively.…”
Section: Womenmentioning
confidence: 99%
“…Keywords: human papillomavirus; pregnancy; follow-up study; natural history; prevalence Several epidemiological and biological studies have established the important role of infection with high-risk types of human papilloma virus (HPV) for development of cervical cancer and its precursor lesions. In women with or without abnormal cervical smears a positive high-risk HPV test result indicates an increased risk for development of high grade cervical lesions (Ho et al, 1995;Remmink et al, 1995;Rozendaal et al, 1996Rozendaal et al, , 2000Nobbenhuis et al, 1999). Moreover, in nearly all cervical cancers high-risk HPV types have been detected .…”
mentioning
confidence: 99%
“…Most infections are transient, with a median duration of at most 12 months, and pose no risk of cervical neoplasia: only the 10-20% that remain persistent are of concern (Ho et al, 1995;Remmink et al, 1995;Nobbenhuis et al, 1999). Evidence of infection, either by serology in stored blood samples or by viral DNA in fixed archival specimens, is found many years before serious disease is present, and indicates that infection precedes disease (Walboomers et al, 1995;Lehtinen et al, 1996;Dillner et al, 1997). Detection of HPV DNA in the absence of cytological abnormalities can also indicate presence of high-grade cervical intraepithelial neoplasia (CIN) which was missed by cytology .…”
Section: Natural Historymentioning
confidence: 99%
“…25 This test has been clinically validated. 11,26,27 Additionally, reverse line blot (RLB) analysis was used to identify individual HPV types in case the PCR-EIA was positive. 25 We used b-globin PCR to identify sampling errors and to monitor for PCR inhibitors.…”
Section: Human Papillomavirus Testingmentioning
confidence: 99%
“…7,8 Persistence of hrHPV infection is required for development of cervical cancer. [9][10][11][12] Several studies have shown that HPV testing has a high sensitivity (approximately 95%) for identifying high-grade lesions and cervical carcinoma. Moreover, the negative predictive value of HPV testing for detection of a high-grade CIN lesion or even (micro)invasive carcinoma is nearly 100%.…”
mentioning
confidence: 99%